2012
DOI: 10.1016/j.trstmh.2011.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Chagas disease in four periurban areas in northeastern Brazil: epidemiologic survey in man, vectors, non-human hosts and reservoirs

Abstract: Chagas disease was investigated in four periurban areas of Ceará state, northeastern Brazil, through serological, parasitological and molecular methods in humans, reservoirs and vectors. A cross-sectional survey revealed a seroprevalence rate of 1.2% (13/1076 residents, six also proving positive through PCR). Trypanosoma cruzi infection was not detected in children under 10 years old. Triatoma pseudomaculata prevailed in the peridomiciles: 63 specimens, 69% (34/49) infected with trypanosomatids. Rhodnius nasut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
2
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 34 publications
3
47
2
11
Order By: Relevance
“…Previous studies have reported detection of mixed TcI and TcVI in human samples in Rio (Sangenis et al, 2015) and in dogs and bugs in northwestern Argentina and the Atlantic forest of Brazil (Marcet et al, 2006;Lima et al, 2014a). Other DTU mixes of TcI and TcIV have been identified in the Brazilian Amazon (Lima et al, 2014b), the United States (Roellig et al, 2013), andin Venezuela (Carrasco et al, 2012); TcI and TcII or TcV have also been reported in mixed infections in Amazonia (Lima et al, 2012). These few studies suggest, however, only minor structuring of T. cruzi on broad geographic scales.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have reported detection of mixed TcI and TcVI in human samples in Rio (Sangenis et al, 2015) and in dogs and bugs in northwestern Argentina and the Atlantic forest of Brazil (Marcet et al, 2006;Lima et al, 2014a). Other DTU mixes of TcI and TcIV have been identified in the Brazilian Amazon (Lima et al, 2014b), the United States (Roellig et al, 2013), andin Venezuela (Carrasco et al, 2012); TcI and TcII or TcV have also been reported in mixed infections in Amazonia (Lima et al, 2012). These few studies suggest, however, only minor structuring of T. cruzi on broad geographic scales.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have highlighted the importance of peridomestic habitats in the re-infestation process by domestic and secondary vectors, oral outbreaks and emergence or re-emergence of Chagas disease in a region [16, 17, 19, 20]. The evaluation of infection levels and the eco-epidemiological roles of domestic, synanthropic and intrusive sylvatic mammals is essential for understanding the epidemiological profile of the disease, the intensity of T. cruzi transmission near homes and the local risk for emergence of human cases [1].…”
Section: Introductionmentioning
confidence: 99%
“…With the aim of contributing to the improvement of triatomine control programs in this endemic region, this study investigates triatomine infestation in peridomicile and intradomicile areas and Chagas disease infection among local residents in a rural locality in an area impacted by human action in the Jaguaribe Valley, State of Ceará 6 . 7 .…”
Section: Introductionmentioning
confidence: 99%